Pemanfaatan Media Wordwall untuk Meningkatkan Minat Belajar dalam Pembelajaran Teori Pjok Siswa Kelas V Sekolah Dasar - Restu Gotama, Made; Sudiana, I Ketut; Danardani, Wasti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to examine the use of Wordwall as an innovative digital tool to enhance the learning interest of fifth-grade students in PJOK theoretical lessons. A qualitative approach using narrative literature review was employed, analyzing scholarly articles, books, and national and international journals related to Wordwall, PJOK learning, and student motivation. The findings revealed that Wordwall effectively presented learning materials in a visual, engaging, and interactive manner through features such as quizzes, games, and instant feedback. The media stimulated students’ affective responses, supported cognitive engagement, and facilitated active knowledge construction. It aligned with principles of affective learning, multimedia integration, and cognitive involvement. Conclusion, wordwall is considered a relevant, contextual, and effective medium for creating meaningful, collaborative, and student-centered theoretical PJOK learning in elementary schools. Keywords: Wordwall, PJOK, learning interest, interactive media, elementary school.